2021
DOI: 10.1039/d0ra10476k
|View full text |Cite
|
Sign up to set email alerts
|

Two novel potent ACEI peptides isolated from Pinctada fucata meat hydrolysates using in silico analysis: identification, screening and inhibitory mechanisms

Abstract: The process of discovering potent angiotensin-converting enzyme inhibitory (ACEI) peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Li et al investigated ACEIPs derived from pearl oyster protein and found that the peptides FRVW (F, V, and W) and LIVT (L, I, and V) contained three hydrophobic amino acids, which exhibited stronger ACE inhibitory activity than peptides with fewer hydrophobic amino acids. 36 This result confirmed the importance of hydrophobic amino acids in ACEIPs.…”
Section: Ace Inhibitory Activity Of Yogurtsupporting
confidence: 64%
“…Li et al investigated ACEIPs derived from pearl oyster protein and found that the peptides FRVW (F, V, and W) and LIVT (L, I, and V) contained three hydrophobic amino acids, which exhibited stronger ACE inhibitory activity than peptides with fewer hydrophobic amino acids. 36 This result confirmed the importance of hydrophobic amino acids in ACEIPs.…”
Section: Ace Inhibitory Activity Of Yogurtsupporting
confidence: 64%
“…Recently, structure−activity studies have suggested that the ACE inhibitory activity of peptides is strongly related to specific amino acid residues in their sequence, particularly hydrophobic amino acids. 24 Also, it has been widely reported that amino acids in the C-terminal position are the most viable to bind ACE, specifically aromatic and hydrophobic residues and proline. 21 Additionally, peptides with 2−12 amino acid residues contribute to ACE inhibitory activity since they may easily bond to the active sites of ACE than larger peptides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…39 In this sense, it is noteworthy to mention that some peptides may possess specific interactions with an allosteric site (a non-active site); changing the structure of the active site and resulting in no enzyme effect. 24 Therefore, further structure−activity relationship studies with these peptides with potential ACE inhibitory effects are necessary. The present study determined the bioaccessibility and bioavailability of ACE inhibitory peptides from FM with L. lactis NRRL B-50571.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 There have been several reports of bioactive peptides that inhibit ACE that were produced by protein hydrolysis and fermentation. 107 Li et al 42 showed that the peptides FRVW and LPYY that were extracted from Pinctada fucata hydrolysates are interesting functional foods for the treatment of high blood pressure and have potential uses as antihypertensive agents. It has been shown that bioactive peptides containing aromatic and aliphatic amino acids, such as Pro, Phe, or Tyr at the C-terminal and Val and Ile at the N-terminal, have ACE-inhibitory action.…”
Section: Applications Of Bioactive Peptides As Functional Food Ingred...mentioning
confidence: 99%